Synthesis of zeolite A in batch and semi-batch reactors - Mat, Ramli; Tavare, N. S. (1997)
Zeolite A is a crystalline aluminosilicate, represented by the formula Na12[(AlO2)12(SiO2)12]27H2O. It has a wide range of applications as ion exchangers. One of these is in a detergent builder where it was suggested in 1970s to replace the phosphate builder for environmental reasons. This crystalline material is usually prepared by combining sources of silica, alumina and alkali to form aluminosilicate gel. Synthesis of zeolite A from sodium aluminate and sodium silicate solutions has been studied using batch and semibatch reactors. The experiments were performed to investigate the effect of the addition rate of sodium silicate solution on zeolite A crystallization. Samples were taken at one hour interval times. The solid samples were analyzed using x-ray diffraction and Scanning Electron Microscope. The addition rate of sodium silicate influenced the nucleation and crystallization rates of zeolite A. Scanning Electron Micrograph of the solid samples indicated a change in the crystal habit and size due to change in the mode of operation from batch to semibatch reactors.